Dance, Art and Yoga in Heather Hansen's work - Laura Molina Vicente (Universitat Autònoma de Barcelona, 2018)
The present article analyzes Kinetic Drawing, a piece developed by Heather Hansen since 2013, in which dance, yoga and painting are fused through performances. It is the result of the search of how to download the movements directly on the paper in an organic way, using the body as the only instrument, yoga and dance as a creative means and meditation as a process of interiorization and dis-intellectualization to initiate artistic development. As a result of this work, combining dance, painting and yoga, we contemplate Heather Hansen's encounter with herself taking the movement of her body as an element of artistic expression.